Em busca da liberdade: uma revisão bibliográfica na Psicologia Analítica - Cavale, Fábio Pipelmo (2018)
This study aimed at identifying those aspects that constitute the concept of freedom under the perspective of Analytical Psychology, presenting a reflection on freedom and its limits in the psychic field, on autonomy and dependence and on the importance of freedom for the individuation process. This work has a theoretical nature and is based on the bibliographical review of the work of Carl Gustav Jung and on the review of articles and books dealing with the theme of freedom. In the literature, from the writings of C.G. Jung on freedom and, later, in the studies of Jungians and post-Jungians on the subject, four categories were identified: Liberty, morality and ethics; Consciousness, complex, unconscious and freedom; Collective consciousness and psychic massification; Individuation process, Self and freedom. The analysis and discussion of the findings suggest that freedom is an important phenomenon for the psychic life, requires responsibility and means taking the direction of one's own actions. Its opposite, defensive freedom, seems to be an escape from responsibility. However, it is not possible to affirm that there is full free will, because unconscious instances, at individual and collective levels, are, at all times, pressing the conscience due to its autonomous functioning. However, the unconscious, as well as collective and group processes can open up a range of possibilities for freedom. The individuation process is a gradual path towards freedom, giving the individual greater awareness of unconscious processes and dynamics of the collective consciousness, and favoring choices that are more conscious and free of determinations, even though in this process the individual needs to make sacrifices. These conclusions point to the clinical importance of the topic